1995
DOI: 10.1111/j.1600-0447.1995.tb09735.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental comorbidity of chronic insomnia in general practice attenders using DSM‐III‐R

Abstract: The major aim of this study was to investigate links between chronic insomnia and mental and personality disorders using the DSM-III-R classification. Of a sample of 2512 general practice attenders, 105 with a chronic insomnia complaint over a 4-month period were evaluated for mental and personality disorders. In addition, the significance of other factors such as personality traits, social functioning and the patient's own estimation of sleep quality was studied. Sixty-six patients got a diagnosis of a curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 21 publications
2
24
1
2
Order By: Relevance
“…Furthermore, in accordance with previous studies with nonstroke patients [11, 39, 43, 44, 45, 46, 47], we found a high frequency of psychiatric comorbidity in our samples of stroke patients with insomnia complaints. About half of the insomniacs met the DSM-IV diagnostic criteria of a depressive disorder and one third that of major depression.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, in accordance with previous studies with nonstroke patients [11, 39, 43, 44, 45, 46, 47], we found a high frequency of psychiatric comorbidity in our samples of stroke patients with insomnia complaints. About half of the insomniacs met the DSM-IV diagnostic criteria of a depressive disorder and one third that of major depression.…”
Section: Discussionsupporting
confidence: 79%
“…In einer ersten Studie, der sog. Mannheimer Allgemeinarztstudie, wurden 2500 Patienten in Allgemeinarztpraxen befragt [33,34,65). Dabei konnten wir zeigen, dass 20% der Patienten über eine Insomnie nach DSM-III-R-Kriterien, d. h. Ein-und Durchschlafstörungen bzw.…”
Section: ᭤ Leitlinie "Nichterholsamer Schlaf"unclassified
“…Longitudinal studies suggest that insomnia increases the risk of developing a psychiatric condition [6,40,41]; these studies also suggest that the treatment of the psychiatric condition does not necessarily resolve disturbed sleep [42,43]. Ohayon [44] examined patients with chronic pain conditions and found 3 times more frequency of insomnia symptoms and more reported daytime impairments due to sleep issues in those with chronic pain in comparison to those with just reported insomnia symptoms.…”
Section: Psychiatric and Medical Comorbiditiesmentioning
confidence: 99%